Enhanced GP training – goals and aspirations. Issue 1 (January 2013) - Simon, Chantal; Riley, Ben
To produce the case for enhancing and extending GP training, the Royal College of General Practitioners (RCGP) sought evidence and submissions from a wide range of professionals, patients and organizations. This evidence was collated and reviewed by an expert group to identify the priority challenges for future general practice, resulting in the identification of a number of key outcomes where future GP training needs to be improved. These outcomes are based on the core roles of the GP in the modern NHS and form the goals and aspirations of enhanced GP training.